Shelf life and Internal Quality of Eggs Coated with Chitosan-Rice bran oil during Storage - Waryat; Winarti Christina; bin Arif Abdullah; Mariana Widayanti Siti; Badrul Jamal Irpan; Hadipernata Mulyana; Sunarmani; Suhirman Sintha; Bahar Syamsu (E3S Web of Conferences)
The shelf life of consumer eggs is only 7-14 days. Chitosan coating technology is one approach for increasing the shelf life of consumer eggs. To boost the hydrophobicity of the chitosan solution, oil must be added. The study sought to investigate the extension of shelf life and internal quality of fresh eggs through cleaning and coating with chitosan and rice bran oil (RBO). Treatments evaluated included controls, cleaners and non-cleaners, coating and non-coating Chitosan, and RBO. Weight loss, egg yolk index, egg white index, haugh units, and pH levels were all recorded. Observations were conducted for seven weeks. The research results showed that coating rice bran oil without sanitizer had the lowest weight loss and egg pH, which were 1.99% and 8.3, respectively. The rice bran oil coating treatment without sanitizer had the greatest egg white and HU indexes, respectively 0.04 and 62.57, while the rice bran oil coating treatment with sanitizer had the highest egg yolk index, 0.32. Without sanitizer, the chitosan and rice bran oil coating treatment outperformed the control and other treatments in terms of egg shelf-life extension.